Enhanced thermoelectric properties of p-type Bi0.5Sb1.5Te3 bulk alloys by electroless plating with Cu and annealing. (June 2016) - Huang, Zhongyue; Dai, Xueting; Yu, Yuan; Zhou, Chongjian; Zu, Fangqiu
Abstract: Copper coated Bi0.5 Sb1.5 Te3 powders were prepared through electroless plating with simplified pretreatment method. After hydrogen reduction, the powders are consolidated into bulk by spark plasma sintering. The lowest lattice thermal conductivity in Bi0.5 Sb1.5 Te3 /Cu reduces to 0.25 W/m·K at 371.5 K after annealing. The figure of merit ( ZT ) of Bi0.5 Sb1.5 Te3 /Cu ascends in a large scale and reaches 1.08 at 373 K and 423 K before and after annealing respectively. The average ZT values of Bi0.5 Sb1.5 Te3 /Cu samples both rise from 0.36 to 0.82, which makes this material suitable for application in a wide temperature range. Graphical abstract: